A checklist of the scale insects (Hemiptera: Coccomorpha) of Kenya, with some new combinations - Watson, Gillian W. (Zootaxa, 2021)
The checklist of scale insect species recorded from Kenya comprises 14 families, 128 genera and 304 species, of which 207 (68.0%) are probably of African origin, 91 (29.9%) have been introduced from outside Africa and six (2.0%) are of unknown origin. Out of the 207 African species, only 11 (5.3%) have been recorded damaging plants, whereas out of the 91 introduced species, 45 (49.5%) have caused or are highly likely to cause plant damage in Kenya. The most economically important scale insect families in Kenya are (in order of importance) the Pseudococcidae, Coccidae and Diaspididae. Four new combinations are made: Eurycoccus glomerulus De Lotto is transferred to Trionymus, as Trionymus glomerulus (De Lotto) comb. n.; Trionymus sativus James is transferred to Paracoccus, as Paracoccus sativus (James) comb. n.; Pseudococcus masakensis James is transferred to Nipaecoccus as Nipaecoccus masakensis (James) comb. n., and Spilococcus commiphorae De Lotto is transferred to Paracoccus, as Paracoccus commiphorae (De Lotto) comb. n.